Ethnic Factors in One Company - Lach, George (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1966)
The purpose of this research project was to visualize the impact of ethnic factors within Canadian National Railways Company. Attention was particularly focused on possible discrimination. Here are presented the research results which seem to be of general interest bearing on such issues as education, language, mobility, promotion, and discrimination.